The theoretical description for aesculetin and quercetin cathodic electrochemical determination in juice - Tkach, Volodymyr; Paiva Martins, Jose Inacio Ferrao; Romanova, Zoriana; Oliveira, Sílvio C. (My University, 2023)
Douro juice is one of the symbols of Portugal. The Douro wine region was first marked in the 18th century. The juice has its characteristic smell and taste, due to the presence of some aromatic lactones. But the main nutritional value of the juice is given by its polyphenol composition. Chestnut C. Sativa is one of the most important products and ingredient for Trás-os-Montes cuisine. Vila Regions - Research on chestnut chemicals and nutritional composition confirms that this fruit is low in fat, cholesterol-free and gluten-free. On the other hand, it is a rich source of starch (carbohydrates), protein, dietary fiber, vitamins, minerals (such as potassium, phosphorus and magnesium), lipids and nutrients. Therefore, it should be investigated. Сік Дору є одним із символів Португалії. Виноробний регіон Дору був першим позначений у XVIII ст. Сік має свій характерний запах і смак, завдяки наявності деяких ароматичних лактонів. Але основну харчову цінність соку надають за своїм поліфенольним складом каштан C. Sativa є одним із найважливіших продуктів і інгредієнт для кухні Trás-os-Montes. Дослідження хімічних речовин каштану та його поживний склад підтверджує, що цей фрукт містить мало жиру, не містить холестерину та глютену. З іншого боку, це багате джерело крохмалю (вуглеводів), білку, клітковини, вітамінів, мінералів (такі як калій, фосфор і магній), ліпідів та інших поживні речовин. Отже має бути дослідженим.
Keywords: сік; поліфеноли; поживні речовини; кухня; напої; каштан; juice; polyphenols; nutrients; cuisine; chestnut drinks; кафедра біотехнології продуктів бродіння і виноробства